2017
DOI: 10.1080/14728222.2017.1397134
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B core protein as a therapeutic target

Abstract: Chronic hepatitis B virus (HBV) infection is difficult to cure, due to the presence of covalently-closed-circular DNA and virus-mediated blunting of host immune response. Existing therapies with nucleos(t)ide analogue or pegylated-interferon are not sufficient to achieve a high rate of HBV surface antigen seroclearance, a more desirable treatment outcome. Novel therapeutic agents targeting alternative viral replication steps are being developed. In this review, we will discuss the hepatitis B core antigen (HBc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 76 publications
1
23
0
1
Order By: Relevance
“…This mechanism of action inhibits infection of hepatocytes in hepatic lobules and formation of cccDNA via either new cell infection or intracellular cccDNA replenishment cycles in cells that are already HBV-infected, phenomena that depend on the production of HBV DNA-containing nucleocapsids. 5,7,8,[10][11][12]20,21 NVR 3-778 appears to have been the first CAM to complete clinical proof-of-concept studies in HBV-infected patients. The phase 1b study results reported here show consistent and concurrent dose-related reductions in serum HBV DNA and RNA levels, as predicted by its novel mechanism of action (ie, inhibition of pgRNA encapsidation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism of action inhibits infection of hepatocytes in hepatic lobules and formation of cccDNA via either new cell infection or intracellular cccDNA replenishment cycles in cells that are already HBV-infected, phenomena that depend on the production of HBV DNA-containing nucleocapsids. 5,7,8,[10][11][12]20,21 NVR 3-778 appears to have been the first CAM to complete clinical proof-of-concept studies in HBV-infected patients. The phase 1b study results reported here show consistent and concurrent dose-related reductions in serum HBV DNA and RNA levels, as predicted by its novel mechanism of action (ie, inhibition of pgRNA encapsidation).…”
Section: Discussionmentioning
confidence: 99%
“…HBc-mediated encapsidation of the viral polymerase and pregenomic HBV RNA (pgRNA) by multimerically assembled viral core (capsid) protein molecules is essential for the production of HBV nucleocapsids and subsequent release of enveloped infectious virus particles from infected cells. [5][6][7] Small molecules have been identified that bind to HBc and can misdirect the assembly of HBc molecules into defective capsid structures, thereby inhibiting pgRNA encapsidation and formation of nucleocapsids and infectious virions. [8][9][10][11] This class of compounds can also inhibit replenishment of intranuclear covalently closed circular DNA (cccDNA) over time, and may have immunomodulatory properties.…”
Section: Methodsmentioning
confidence: 99%
“…In comparison to NAs, CpAMs have distinct modes of action; for example, they inhibit pgRNA encapsidation and cccDNA formation, presumably by inhibiting the capsid uncoating step. (73,74) The first compound studied in humans was NVR3-778; in a dose ranging phase Ib study, serum HBV DNA and HBV RNA decreased but a decline in HBsAg was mainly observed when combined with PEG-IFN. (75) Several CpAMs are in preclinical and clinical studies (Table 2).…”
Section: Nucleocapsid Assembly and Pgrna Packagingmentioning
confidence: 99%
“…In comparison to NAs, CpAMs have distinct modes of action; for example, they inhibit pgRNA encapsidation and cccDNA formation, presumably by inhibiting the capsid uncoating step. 77,78 The first compound studied in humans was NVR3-778; in a dose ranging phase Ib study, serum HBV DNA and HBV RNA decreased but a decline in HBsAg was mainly observed when combined with PEG-IFN. 79 Several CpAMs are in preclinical and clinical studies ( Table 2).…”
Section: Inhibition Of Gene Expressionmentioning
confidence: 99%